The Romance of the Reaper - Casson, Herbert Newton, 1869-1951 (Salt Lake City, UT : Project Gutenberg, 2010)
"The Romance of the Reaper" by Herbert Newton Casson is a historical account written in the early 20th century. This work delves into the invention and impact of the reaper, a revolutionary machine that transformed agriculture and significantly influenced the prosperity of the United States. The narrative likely explores the lives of key figures in the development of this technology, including Cyrus Hall McCormick, whose innovations helped to alleviate hunger and poverty. At the start of the book, readers are introduced to the historical context surrounding the invention of the reaper. Casson paints a vivid picture of the plight of farmers before the advent of mechanized harvesting, highlighting how laborious grain harvesting was before the reaper was developed. The narrative outlines Cyrus McCormick's journey from a young inventor facing skepticism to becoming a pivotal figure in American agriculture, sharing anecdotes that showcase the initial challenges and triumphs of introducing this life-changing technology to farmers and society at large. The opening sets the stage for a grand exploration of the machine's historical significance and its contribution to economic and social progress in America. (This is an automatically generated summary.)
The story of McCormick -- The story of Deering -- The International Harvester Company -- The American harvester abroad -- The harvester and the American farmer.
Release date is 2010-06-05
E-text prepared by Tom Roch and the Project Gutenberg Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by the Core Historical Literature of Agriculture (CHLA), Albert R. Mann Library, Cornell University (http://chla.library.cornell.edu/) and Internet Archive/American Libraries (http://www.archive.org/details/americana)
Keywords: Harvesting machinery